2018
DOI: 10.1163/15685411-00003148
|View full text |Cite
|
Sign up to set email alerts
|

On the morphometric identity of populations of Helicotylenchus pseudorobustus (Steiner, 1914) Golden, 1956 (Tylenchida: Hoplolaimidae)

Abstract: Summary Helicotylenchus microlobus is considered to be a junior synonym of H. pseudorobustus by several authors while others consider it as valid. To clarify the status of both species, 39 samples collected from various countries were subjected to statistical analyses that showed they could be grouped into six groups. Topotypes of H. pseudorobustus and H. microlobus belong to two different groups. However, samples in the other groups were morphologically intermediate between these two groups. Characters used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Some culture methods for plant-parasitic nematodes have been successfully employed, but there have been great differences in culture techniques. For example, Aphelenchoides besseyi, Ditylenchus destructor and Bursaphelenchus xylophilus can be cultured on certain fungi [31][32][33]. A. ritzemabosi and D. dipsaci can reproduce rapidly on alfalfa tissue [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some culture methods for plant-parasitic nematodes have been successfully employed, but there have been great differences in culture techniques. For example, Aphelenchoides besseyi, Ditylenchus destructor and Bursaphelenchus xylophilus can be cultured on certain fungi [31][32][33]. A. ritzemabosi and D. dipsaci can reproduce rapidly on alfalfa tissue [19].…”
Section: Discussionmentioning
confidence: 99%
“…The sequences obtained for H. californicus grouped with an isolate of Helicotylenchus from Calathea not identified to the species level and labeled as CD761 in Subbotin et al (2015) ( Table 7 ). Recently, Fortuner et al (2018) identified isolate CD761 as H. pseudorobustus using morphological and morphometric analysis. However, our populations are similar to preliminary reports of H. californicus ( Van Den Berg and Heyns, 1975 ; Krall, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulated status of Ditylenchus spurred widespread research, which led to the discovery of numerous new species without giving adequate consideration to the limits of species variability [27]. Several taxonomists have reviewed the genus characteristics in attempts to limit the number of valid species by revisions and synonymization [3,27,28]. More recently, Hashemi and Karegar [16] updated the entire genus Ditylenchus and documented 60 nominal species; presently, the genus contains 63 species.…”
Section: Introductionmentioning
confidence: 99%
“…Further morphological comparisons revealed their identity as D. anchilisposomus (Tarjan) Fortuner [28,40], D. clarus Thorne and Malek [31], D. tenuidens Gritsenko [41], and D. valveus. All of these species are new records in Canada except for the D. valveus.…”
Section: Introductionmentioning
confidence: 99%